Sistem Informasi Sekolah Pada SMK Kader Pembangunan - Joko Kuswanto; M. Ilham Maulidan; Jovanca Esha Nandini; M. Ikhsan Abdi Rabani; Putu Agus Indra Yoga; M. Erick Deppiko Syaputra (Informatics Study Program, Faculty of Engineering and Computers, Baturaja University, 2021)
Speaking more about school information systems, today there are many computer applications that are devoted to the creation of applications, for example Mirosoft Access, Borland Delphi, and Visual Basic or web-based. But, in fact in SMK Kader Pembangunan Baturaja school data processing has not used computer-based application programs. This research aims to create a school information system in SMK Kader Pembangunan. The research method used is by waterfall method. This system is expected to facilitate and speed up the process of collecting, processing, and managing data or information, and support the implementation of teaching and learning in schools.